A systematic review of the word sentence association paradigm (WSAP). (September 2019) - Gonsalves, Meghan; Whittles, Randy L.; Weisberg, Risa B.; Beard, Courtney
Abstract: Background and objectives: The Word Sentence Association Paradigm (WSAP) was originally designed to assess and modify interpretive biases (IB) in socially anxious individuals. Researchers have since modified the WSAP for use across various populations. Despite its widespread use, no studies have systematically reviewed the WSAP to determine its validity and reliability. Methods: We review variations to the WSAP, populations in which the WSAP has been used, reliability data, and effect sizes across 41 studies published between 2008 and March 2018. Results: Results indicate that the WSAP has been utilized to target 18 disorders and symptoms in adults and children. Modifications include stimulus content, timing parameters, and presentation order of word and sentence pairs. Reported internal consistency and test-retest reliability suggest good to excellent reliability. Medium to large effect sizes were reported when comparing control samples to those with psychopathology and in pre-post comparisons of the modification version of the WSAP. Limitations: Studies varied regarding which indices of the WSAP were presented and specific task parameters used, making it challenging to compare effects. Conclusions: The WSAP is a reliable and valid instrument for assessing and modifying interpretive biases with unique characteristics compared with other IB assessment and modification tasks. Highlights: Reviewed 41 studies that used the WSAP. WSAP showed good reliability and validity. CBM-I version of WSAP showed large pre-post training effect sizes.